2000
DOI: 10.1074/jbc.m000840200
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Control of Smooth Muscle-specific Gene Expression through Regulated Nuclear Translocation of Serum Response Factor

Abstract: Prolonged serum deprivation induces a structurally and functionally contractile phenotype in about 1/6 of cultured airway myocytes, which exhibit morphological elongation and accumulate abundant contractile apparatus-associated proteins. We tested the hypothesis that transcriptional activation of genes encoding these proteins accounts for their accumulation during this phenotypic transition by measuring the transcriptional activities of the murine SM22 and human smooth muscle myosin heavy chain promoters durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 57 publications
2
83
2
Order By: Relevance
“…Previous work with ASM cells suggests that the stimulation of contractile protein gene expression requires the binding of SRF to the CArG box present in specific gene promoters (28). We show here that FGF-2 does not attenuate the TGF-b-stimulated increase of an artificial promoter that solely contains CArG sites and a minimal TATA, suggesting that other partners are needed in addition to SRF to elicit FGF-2 inhibitory functions (P .…”
Section: Srf-dna Binding Activity Is Insufficient For the Inhibitory mentioning
confidence: 61%
“…Previous work with ASM cells suggests that the stimulation of contractile protein gene expression requires the binding of SRF to the CArG box present in specific gene promoters (28). We show here that FGF-2 does not attenuate the TGF-b-stimulated increase of an artificial promoter that solely contains CArG sites and a minimal TATA, suggesting that other partners are needed in addition to SRF to elicit FGF-2 inhibitory functions (P .…”
Section: Srf-dna Binding Activity Is Insufficient For the Inhibitory mentioning
confidence: 61%
“…Nuclear extractions were prepared using a standard protocol (19). Doublestranded oligonucleotide probes were generated by annealing complementary synthetic oligonucleotides and end-labeling with T4 polynucleotide kinase (New England Biolabs) and [␥-32 P] ATP (Amersham Biosciences).…”
Section: Emsamentioning
confidence: 99%
“…Several mechanisms have been shown to regulate the SRF transcription activity, including physical interaction of SRF with a number of positive and negative cofactors (6 -10), phosphorylation-dependent change in the DNA and/or protein binding ability of SRF (18), regulated nuclear translocation of SRF (19), and alternative splicing of SRF mRNA primary transcript (20,21). Recently, we have shown that an alternative spliced isoform of SRF is highly expressed in the failing hearts of both humans and animals, which act as a dominant negative isoform to repress SRF-dependent cardiac muscle gene expression (22).…”
mentioning
confidence: 99%